Persistent spectral hole burning and optical properties of Sm2+ doped in Mg0.5Sr0.5FCl0.5Br0-5 mixed crystal - Jang, KW; Kim, IG; Seo, HJ; Moon, BK; Bae, HS; Yu, BY; Lee, JI; Pyun, CH; Kim, CH (PHYSICAL SOC JAPAN, 2001)
A Sm2+-containing Mg0.5Sr0.5FCl0.5Br0.5 mixed crystal was synthesized by firing at 1,100 degreesC 2 hours in a reducing stream of hydrogen gas and examined with an X-ray diffractometer for the crystalline structure. We measured the optical properties of Sm2+-ion and observed the efficiencies of persistent spectral hole burning depend on hole burning methods at 90 K and 300 K. At 90 K, PSHB was made much more efficiently by using the photon-gated (two color) spectral hole burning process compared to the one color hole burning process, while the one color hole burning process is much more efficient at 300 K.
Keywords: SILICATE-GLASSES; FLUORESCENCE; PHOTOIONIZATION